2020
DOI: 10.3390/ijms21114091
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Landscape in Pancreatic Ductal Adenocarcinoma: On the Way to Overcoming Drug Resistance?

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive solid malignancies due to the rapid rate of metastasis and high resistance to currently applied cancer therapies. The complex mechanism underlying the development and progression of PDAC includes interactions between genomic, epigenomic, and signaling pathway alterations. In this review, we summarize the current research findings on the deregulation of epigenetic mechanisms in PDAC and the influence of the epigenome on the dynamics of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 103 publications
0
17
0
Order By: Relevance
“…Genomic instability can occur at both, the genetic and epigenetic level ( Putiri and Robertson, 2011 ) and it increases as the tumor progresses. Epigenetics refers to the control of gene expression without changing the DNA sequence, e.g., via chemical modifications like methylation of the DNA, that can be passed on in cell divisions ( Jones and Baylin, 2007 ; Akhavan-Niaki and Samadani, 2013 ; Ciernikova et al, 2020 ; Alonso-Curbelo et al, 2021 ). Epigenetic changes like gene silencing by promoter hypermethylation or gene overexpression by promoter hypomethylation were shown to impact cancer progression ( Jones and Baylin, 2007 ).…”
Section: Epigenetic Alterations Drive Pdac Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic instability can occur at both, the genetic and epigenetic level ( Putiri and Robertson, 2011 ) and it increases as the tumor progresses. Epigenetics refers to the control of gene expression without changing the DNA sequence, e.g., via chemical modifications like methylation of the DNA, that can be passed on in cell divisions ( Jones and Baylin, 2007 ; Akhavan-Niaki and Samadani, 2013 ; Ciernikova et al, 2020 ; Alonso-Curbelo et al, 2021 ). Epigenetic changes like gene silencing by promoter hypermethylation or gene overexpression by promoter hypomethylation were shown to impact cancer progression ( Jones and Baylin, 2007 ).…”
Section: Epigenetic Alterations Drive Pdac Progressionmentioning
confidence: 99%
“…Epigenetic drugs were shown to reduce tumorigenicity in pre-clinical models and some are already used in clinical trials ( Hessmann et al, 2017 ; Ciernikova et al, 2020 ; Morel et al, 2020 ). However, so far, they are associated with limited efficacy and not successful as monotherapy.…”
Section: Epigenetic Alterations Drive Pdac Progressionmentioning
confidence: 99%
“…The complex interaction between genomic, epigenomic, and signaling pathway alterations affect PDAC growth and progression [ 136 ]. It has been shown that the EMT leads to the malignant phenotype in PCSCs.…”
Section: Role Of Epigeneticsmentioning
confidence: 99%
“…Epigenetic changes, which are strongly affected by hypoxia, are an important feature of cancer development and progression [126]. Hypoxia upregulates the expression of different DNA methylation and demethylation enzymes.…”
Section: Clinical Significance Of Caix In Pancreatic Cancermentioning
confidence: 99%
“…Cooperation between hypoxia stimuli and paracrine signaling from an inflammatory environment, an inherent feature of pancreatic tumors, induces EMT, stemness, and promotes the formation of circulating tumor cells [126]. High CAIX expression was detected in tumor-initiating cells (TICs) positive for pancreatic cancer stem cell markers EpCAM + /CD44 + /CD24 + , isolated from PDAC patient samples [29].…”
Section: Influence Of Caix Expression and Caix-associated Tumor Micromentioning
confidence: 99%